The boundaries of pedagogical research in the realm of «Physical education for students» the emphasis of the articles in the journal «Theory and practice of physical culture» - Lubysheva L.I.; Minnikaeva N.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to delineate the boundaries of pedagogical understanding in the area of «physical education for students» through a comprehensive review of empirical studies published in the journal «Theory and Practice of Physical Culture». Methods and structure of the study. A comprehensive analysis of articles published in the journal «Theory and Practice of Physical Culture» between 2020 and 2024 was conducted. The analysis sought to answer two questions: 1. What pedagogical phenomena in the field of physical education of students are discussed in these articles? 2. Which pedagogical technologies in the field of physical education of students have been proven to be effective and are among the top 10% in terms of their impact? The final database for the first question includes 27 articles, while the second question was answered based on 41 articles, which included empirical data with significant content. Results and conclusions. The research paper delineates the boundaries of pedagogical expertise in the realm of physical education for students, as exemplified by the articles published in the journal Theory and Practice of Physical Culture. These boundaries encompass the following aspects: The concept of health promotion, which encompasses health preservation, health enhancement, and health development. The humanistic approach to improving the physical culture of students, emphasizing the importance of personal growth and self-actualization. The existential perspective on physical education, which prioritizes individual choice and autonomy. Innovative educational approaches in the field of physical education for students. Local research initiatives in specific areas of physical education, which may not receive widespread attention due to their limited impact. The study is a relevant account for establishing a fresh publishing strategy for the TPPC magazine, encompassing the advancement of scholarly material in the realm of physical culture and sports, and serving as a blueprint for exploring diverse facets of sports science.